Implementasi Protokol Triage START: Dampaknya Terhadap Prioritas Penanganan Pasien Gawat Darurat - Rahagia, Rasi (Asosiasi Guru dan Dosen Seluruh Indonesia, 2025)
Emergency care requires healthcare workers to assess and prioritize patient care quickly and accurately to prevent potentially fatal delays in medical intervention. One widely used triage method is Simple Triage and Rapid Treatment (START), which assesses patient condition based on respiration, perfusion, and mental status. This study aims to determine the impact of implementing the START triage protocol on the accuracy of prioritization of emergency patient care in the Emergency Department (ED). This study used a quantitative pre-experimental design with a one-group pretest–posttest approach. The sample consisted of 40 healthcare workers working in the Emergency Department of Hospital X, selected using a total sampling technique. Data were collected through observation sheets and an assessment instrument for triage priority accuracy before and after the implementation of the START protocol. Data were analyzed using paired t-tests or Wilcoxon tests with a significance level of α = 0.05. The results showed a significant improvement in the accuracy of prioritization of emergency patient care after the implementation of the START triage protocol. The statistical test results showed a p-value of 0.001 (<0.05), indicating a significant difference between the accuracy of treatment priorities before and after the implementation of the START protocol. The conclusion of this study is that the implementation of the START triage protocol is effective in improving the accuracy of treatment priorities for emergency patients. Consistent implementation of the START protocol can be an important strategy for improving the quality of emergency care and patient safety in the ED.